Characterisation of NADH fluorescence properties under one-photon excitation with respect to temperature, pH and binding to lactate dehydrogenase - Cannon,T; Lagarto,J; Dyer,B; Garcia,Castano E; Kelly,D; Peters,N; Lyon,A; French,P; Dunsby,C (Optical Society of America Continuum, 2021)
Reduced nicotinamide adenine dinucleotide (NADH) is the principal electron donor in glycolysis and oxidative metabolism and is thus recognized as a key biomarker for probing metabolic state. While the fluorescence characteristics of NADH have been investigated extensively, there are discrepancies in the published data due to diverse experimental conditions, instrumentation and microenvironmental parameters that can affect NADH fluorescence. Using a cuvette-based time-resolved spectrofluorimeter employing one-photon excitation at 375 nm, we characterized the fluorescence intensity, lifetime, spectral response, anisotropy and time-resolved anisotropy of NADH in aqueous solution under varying microenvironmental conditions, namely temperature, pH, and binding to lactate dehydrogenase (LDH). Our results demonstrate how temperature, pH, and binding partners each impact the fluorescence signature of NADH and highlight the complexity of the fluorescence data when different parameters produce competing effects. We hope that the data presented in this study will provide a reference for potential sources of variation in experiments measuring NADH fluorescence.